Child Drug Abuse: Factors, Judicial Process, and Legal Protection - Sidiq, Fahmi; binti Abdullah Suhaimi, nurnisaa; prabowo, agung (Communication in Research and Publications (CRP), 2023)
Drug abuse among children is a serious issue that requires special attention. This article discusses the factors that influence children from engaging in drug abuse, the judicial proceedings against them, and the legal protections provided. The research method used is a normative legal research method with a qualitative approach. The results showed that peer factors, personality, psychiatric conditions, family, and the availability of narcotics in the market play an important role in narcotics abuse. The juvenile justice process for drug abusers goes through several stages, including investigation, prosecution, trial, and formation at the Special Child Development Institute. Legal protection for children is regulated in the Child Protection Law and the Juvenile Criminal Justice System Law. The adverse effects of the formal criminal justice process are also discussed, including trauma, stigma, and exclusion from school. Diversion programs are an important alternative to protect children from the negative consequences of the formal criminal justice process.